Penerapan Kriptografi Caesar Cipher Pada Fitur Aplikasi Chatting Whatsapp - Kiki Andrea; Aji Wardana; Bagus Sopian Wanandi; Ali Ikhwan (Jurnal Penelitian Dan Pengkajian Ilmiah Eksakta, 2023)
At this time chat has been considered as a facility that can be used to communicate directly both remotely and at close range. Those who must be connected online with internet users around the world. In this case, this research will be applied to the WhatsApp text messaging application using the method applied, namely Caesar cipher cryptography. The system development method that will be used for this research is the prototype method. The results obtained from this research method are chat messages on the WhatsApp application encrypted using Caesar cipher cryptography with message encryption using end-to-end processing techniques where encryption and message descriptions can be done while chatting.